Concurrent arterial aneurysms in brain arteriovenous malformations with haemorrhagic presentation. Issue 3 (1st September 2002) - Stapf, C; Mohr, J P; Pile-Spellman, J; Sciacca, R R; Hartmann, A; Schumacher, H C; Mast, H
Abstract : Objective: To assess the effect of concurrent arterial aneurysms on the risk of incident haemorrhage from brain arteriovenous malformations (AVMs). Methods: In a cross sectional study, 463 consecutive, prospectively enrolled patients from the Columbia AVM Databank were analysed. Concurrent arterial aneurysms on brain angiography were classified as feeding artery aneurysms, intranidal aneurysms, and aneurysms unrelated to blood flow to the AVM. Clinical presentation (diagnostic event) was categorised as intracranial haemorrhage proved by imaging or non-haemorrhagic presentation. Univariate and multivariate statistical models were applied to test the effect of age, sex, AVM size, venous drainage pattern, and the three types of aneurysms on the risk of AVM haemorrhage at initial presentation. Results: Arterial aneurysms were found in 117 (25%) patients with AVM (54 had feeding artery aneurysms, 21 had intranidal aneurysms, 18 had unrelated aneurysms, and 24 had more than one aneurysm type). Intracranial haemorrhage was the presenting symptom in 204 (44%) patients with AVM. In the univariate model, the relative risk for haemorrhagic AVM presentation was 2.28 (95% confidence interval (CI) 1.12 to 4.64) for patients with intranidal aneurysms and 1.88 (95% CI 1.14 to 3.08) for those with feeding artery aneurysms. In the multivariate model an independent effect of feeding artery aneurysms (odds ratio 2.11, 95% CI 1.18 to 3.78) on haemorrhagic AVM presentation was found. No significant effect was seen for intranidal and unrelated aneurysms. The attributable risk of feeding artery aneurysms for incident haemorrhage in patients with AVM was 6% (95% CI 1% to 11%). Conclusions: The findings suggest that feeding artery aneurysms are an independent determinant for increased risk of incident AVM haemorrhage.